Gambaran Status Gizi dan Upaya Preventif Anemia pada Remaja Putri di SMAN 8 Kota Jambi - Azlita, Dara; Hesty, Hesty; Iswanto, Iswanto (Prosiding Seminar Kesehatan Nasional, 2024)
Anemia is a decrease in the amount of erythrocyte mass, which is indicated by a decrease in hemoglobin, hematocrit, and erythrocyte count. One of the health problems that often occurs in adolescents, especially adolescent girls, is anemia. The prevalence of anemia in Indonesia at the age of 15-24 years is 32.0%. The incidence of anemia from the data of the puskesmas SMAN 8 Jambi City was 37 adolescent girls. Some factors that can cause anemia are nutritional status, consumption patterns, physical activity and compliance with blood supplement tablets consumption. Therefore, overcoming and preventing anemia in adolescent girls is a health problem that is focused on by the government. The purpose of the study was to determine the description of nutritional status and preventive efforts of anemia in adolescent girls at SMAN 8 Jambi City. This type of research is quantitative research, using a descriptive design. The research time was conducted from March to July 2024 which was located at SMAN 8 Jambi City. The sample in this study were adolescent girls affected by anemia at SMAN 8 Jambi City, totaling 37 adolescent girls in grades X and XI. Data collection techniques using total sampling techniques. Data collection techniques by filling out questionnaires, measuring height and weight. Data analysis in the study using univariate data analysis. The results of this study indicate that normal nutritional status (43.2%), efforts to prevent anemia are sufficient (45.9%), adherence to the consumption of blood supplement tablets that are not obedient (91.9%). In this study it can be concluded that for adolescent girls can make efforts to prevent anemia early on by changing a good diet, taking blood tablets to reduce the incidence of anemia in adolescent girls.